Prevalence of and risk factors for severe malaria caused by Plasmodium and dengue virus co-infection: a systematic review and meta-analysis - Manas Kotepui; Kwuntida Uthaisar Kotepui; Giovanni De Jesus Milanez; Frederick Ramirez Masangkay (BMC, 2020)
Abstract Background Co-infection with both Plasmodium and dengue virus (DENV) infectious species could have serious and fatal outcomes if left undiagnosed and without timely treatment. The present study aimed to determine the pooled prevalence estimate of severe malaria among patients with co-infection, the risk of severe diseases due to co-infection, and to describe the complications of severe malaria and severe dengue among patients with co-infection. Methods Relevant studies published between databases between 12 September 1970 and 22 May 2020 were identified and retrieved through a search of the ISI Web of Science, Scopus, and MEDLINE. The pooled prevalence and 95% confidence interval (CI) of severe malaria among patients with Plasmodium and DENV co-infection was estimated with a random-effects model to take into account the between-study heterogeneity of the included studies. The risks of severe malaria and severe diseases due to co-infection were estimated with the pooled odds ratio (OR) and 95% CI with a random-effects model. Results Of the 5653 articles screened, 13 studies were included in the systematic review and meta-analysis. The results demonstrated that the pooled prevalence estimate of severe malaria among patients with co-infection was 32% (95% CI: 18-47%, I 2 = 92.3%). Patients with co-infection had a higher risk of severe diseases than those with DENV mono-infection (odds ratio [OR] = 3.94, 95% CI: 1.96-7.95, I 2 = 72%). Patients with co-infection had a higher risk of severe dengue than those with DENV mono-infection (OR = 1.98, 95% CI: 1.08-3.63, I 2 = 69%). The most severe complications found in severe dengue were bleeding (39.6%), jaundice (19.8%), and shock/hypotension (17.9%), while the most severe complications found in severe malaria were severe bleeding/bleeding (47.9%), jaundice (32.2%), and impaired consciousness (7.43%). Conclusions The present study found that there was a high prevalence of severe malaria among patients with Plasmodium and DENV co-infection. Physicians in endemic areas where these two diseases overlap should recognize that patients with this co-infection can develop either severe malaria or severe dengue with bleeding complications, but a greater risk of developing severe dengue than severe malaria was noted in patients with this co-infection. Trial registration The protocol of this study was registered at PROSPERO: CRD42020196792 .